KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG - Sella Safriana Geby; Nina Widowati; Dyah Hariani (Journal of Public Policy and Management Review, 2013)
Health is one of the most important element of quality of life in national development to realize the whole Indonesian people. Rowosari health center is organization that provides health care for its people. This study aims to find out and get a clear picture about the quality of services provided by Public Health Care of Rowosari. This study used a qualitative descriptive type, to mind than 8 dimension service. The results showed that the quality of health services at the health center Public Health Care of Rowosari District Tembalang less good, it is proved from the result of the interview which showed that dimension tangibes, reliability and empathy has not been going well and inadequate. To improve the service, the health service center in Rowosari have to repair the building and add some seats in the waiting room for the patients. Employee must also provide 3 S (smile, great, greetings) to patients from the beginning of opening service until done.